Trends in antenatal HIV prevalence in urban Uganda associated with uptake of preventive sexual behaviour. (30th March 2006) - Kirungi, W L; Musinguzi, J; Madraa, E; Mulumba, N; Callejja, T; Ghys, P; Bessinger, R
Abstract : Background: Epidemiological surveillance in Uganda has consistently shown declining HIV prevalence particularly among young antenatal women since the early 1990s, correlated with increased uptake of protective sexual behaviour. Objective: To describe trends in sexual behaviour nationwide and antenatal HIV prevalence from urban sentinel sites in Uganda (1989–2002). Methods: Review of antenatal HIV seroprevalence data from the sentinel surveillance system (1989–2002) and data on sexual behavioural indicators from the AIDS module of the National Demographic and Health Surveys (1989, 1995 and 2000/01). Trends in biological and behavioural indicators assessed. Results: Antenatal HIV seroprevalence in seven urban clinics peaked around 1992 (15–30%) followed by a steady decline by 2002 (5–12%), most markedly among women aged 15–19 and 20–24 years. This coincided with increased primary and secondary abstinence among young people nationwide. Median age at sexual debut increased from 16.5 in 1989 to 17.3 in 2000 for women and from 17.6 in 1995 to 18.3 in 2000 for men. Premarital sex among women and multiple partnerships decreased between 1995 and 2000. There were no significant changes in reporting of extramarital sex among men. Ever use of condoms increased from 1% among women in 1989 and 16% among men in 1995 to 16% and 40% in 2000, respectively. Between 1995 and 2000, condom use at last sex with a non-regular partner increased from 35% to 59% and 20% to 39% among men and women, respectively. Conclusion: The ecological correlation between the trends in HIV prevalence and incidence and the increase in protective sexual behaviour during the 1990s makes a compelling case for continuing prevention efforts in Uganda.